Penelitian tentang ukuran acuan sepatu wanita dewasa Indonesia - Bandi, Sri; Soewandi, Soewandi; Basuki, Dwi Asdono (Center for Leather, Rubber, and Plastic Ministry of Industry, Indonesia, 1996)
Research was carried out towards 1.883 Indonesia women which covers the provinces of DKI Jaya, West Java, Center Jawa, the Special Territory of Yogyakarta and East Java.The taken samples were unrestricted to variables (for instance, tribe, respondent origin, body weight and bodytall). From the overoll of the respondents, to analysis of data, it was randomly taken to the amount of 50 footÂ Â Â Â Â Â Â Â Â Â size samples.The result of the research showed that the Indonesian women have the shoe size from No. 33 PP up to and including No. 37 PP with the average is 35 PP. The instep size ranged among B, C, D, E, F, G. In this caseÂ there is no obviously difference to the Versterâs finding which states thatÂ the foot instep size of Europen women have the notation among C,D,E,F,G,H.Â Â INTISARIÂ Penelitian dilakukan terhadap 1.883 Wanita Dewasa Indonesia, meliputi daerah DKI Jaya, Jawa Barat, Jawa Tengah, Daerah Istimewa YogyakartaÂ Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â dan Jawa Timur.Sampel yang diambilÂ tidak dibatasi oleh variabel (misal suku bangsa, asal responden, berat badan dan tinggi badan). Dari keseluruhan responden untuk analisa data diambil secara random sejumlah 50 sampel ukuran kaki.Hasil penelitian menunjukkan bahwa Wanita Dewasa Indonesia mempunyai ukuran sepatu dari No. 33 PP sampai dengan No. 37 PP dengan rata-rata 35 PP. Ukuran gemuk berkisar antara B, C, D, E, F, G. Hal ini tidak terdapat perbedaan yang nyata dengan pendapat VersterÂ yang mengatakan ukuran gemuk kaki Wanita Dewasa mempunyai notasi antara C, D, E, F, G, H.Â